Association between carbohydrate consumption with telomere length based on plasma malondialdehyde in Minangkabau male - Nazulis, Weni F.; Sulastri, Delmi; Lestari, Yuniar (International Journal of Research in Medical Sciences, 2019)
Background: Life expectancy was one indicator of human development index in the health sector, one of which was affected by the telomere shortening process. There were many factors that cause shortening of telomere, including an imbalance of carbohydrate consumption then oxidative stress. The study aimed to examine the association between carbohydrate and carbohydrate simplex (sucrose) consumption with telomere length based on plasma malondialdehyde in Minangkabau male. Methods: The study was cross-sectional with 97 samples from male civil servant, Minangkabau ethnic, 40-50 years old in Padang City. Carbohydrate and sucrose consumptions were obtained through semiquantitative food frequency questionnaire, plasma malondialdehyde examination with thiobarbituric acid test and telomere length measured by quantitative polymerase chain reaction using O’Challagan and Fenech method. Results: The result showed mean of telomere length was 550.43±188.47 bp; mean of carbohydrate consumption 1280.97±433.57 kcal or 48.80±16.52%; mean of sucrose consumption 179.40±126.61 kcal or 6.83±4.82% and mean plasma malondialdehyde 66.91±13.93 nmol/ml. The association of carbohydrate consumption with telomere length based on plasma malondialdehyde was obtained p-value = 0.714, 0.908 and 0.903. The relationship of sucrose consumption with telomere length based on malondialdehyde was obtained p-value=0,667 and 1,000. Differences in mean telomere length in various categories of carbohydrate and sucrose consumption obtained p-value = 0.547 and 0.559. Conclusions: There was no significant association between carbohydrate and carbohydrate simplex (sucrose) consumption with telomere length based on plasma malondialdehyde of Minangkabau male; and no significant difference in telomere length in different categories of carbohydrate consumption and different sucrose consumption.